Phenotypic and Genotypic Identification of Antimicrobial Resistance amongst the Campylobacter jejuni and Campylobacter coli Strains Isolated from Raw Milk of Animal Species - Gholamreza Banisharif Dehkordi; Mohammad Hossein Marhamatizadeh; Hassan Momtaz (Journal of Food Quality)
Campylobacter jejuni and Campylobacter coli portion as an important food-borne pathogen owing to the consumption of raw milk of animal species is unmoving unidentified. This survey appraised both phenotypic and genotypic patterns of antimicrobial resistance amongst the C. jejuni and C. coli strains isolated from raw milk samples. Totally, 850 raw milk samples were examined for C. jejuni and C. coli. After culture, species identification was done using PCR. Phenotypic and genotypic patterns of antimicrobial resistance were assessed using disk diffusion and PCR, respectively. One hundred and ten out of 850 (12.94%) raw milk samples were contaminated with Campylobacter spp (95% confidence interval). The highest contamination rate with Campylobacter spp. was observed in raw cow milk (18.18%). C. jejuni and C. coli species were detected in 45.45% and 32.72% of Campylobacter isolates, respectively (P<0.05). C. jejuni strains showed the highest resistance rate toward tetracycline (84%), gentamicin (80%), ampicillin (74%), and erythromycin (64%). Similarly, C. coli isolates showed the highest resistance rate toward tetracycline (63.88%), gentamicin (58.33%), and ampicillin (52.77%). The lowest resistance rate of C. jejuni and C. coli was observed against chloramphenicol (10% and 2.77%), nalidixic acid (22% and 8.33%), clindamycin (36% and 13.88%), and ciprofloxacin (38% and 16.66%), respectively. The most routinely identified antimicrobial resistance genes amongst the C. jejuni isolates were tetA (66%), blaOXA−61 (54%), tetO (46%), and tetB (40%), while those of C. coli isolates were blaOXA−61 (52.77%), tetA (41.66%), cmeA (27.77%), and tetO (27.77%). The prevalence of simultaneous resistance toward more than 4 antimicrobial agents amongst the C. jejuni and C. coli isolates was 46% and 16.66%, respectively. C. jejuni and C. coli average multiple antimicrobial resistance (MAR)-indexes in the present research were 0.49 and 0.32, respectively. The simultaneous presence of phenotypic and genotypic profiles of antimicrobial resistance amongst the resistant C. jejuni and C. coli bacteria suggests an imperative threat rendering contaminated raw milk consumption and probable occurrence of campylobacteriosis.